No differences in ventral striatum responsivity between adolescents with a positive family history of alcoholism and controls. (5th June 2014) - Müller, Kathrin U.; Gan, Gabriela; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Büchel, Christian; Conrod, Patricia; Fauth‐Bühler, Mira; Flor, Herta; Gallinat, Jürgen; Garavan, Hugh; Gowland, Penny; et al.
Abstract Individuals with alcohol‐dependent parents show an elevated risk of developing alcohol‐related problems themselves. Modulations of the mesolimbic reward circuit have been postulated as a pre‐existing marker of alcoholism. We tested whether a positive family history of alcoholism is correlated with ventral striatum functionality during a reward task. All participants performed a modified version of the monetary incentive delay task while their brain responses were measured with functional magnetic resonance imaging. We compared 206 healthy adolescents (aged 13–15) who had any first‐ or second‐degree relative with alcoholism to 206 matched controls with no biological relative with alcoholism. Reward anticipation as well as feedback of win recruited the ventral striatum in all participants, but adolescents with a positive family history of alcoholism did not differ from their matched peers. Also we did not find any correlation between family history density and reward anticipation or feedback of win. This finding of no differences did not change when we analyzed a subsample of 77 adolescents with at least one parent with alcohol use disorder and their matched controls. Because this result is in line with another study reporting no differences between children with alcohol‐dependent parents and controls at young age, but contrasts with studies of older individuals, one might conclude that at younger age the effect of family history has not yet exerted its influence on the still developing mesolimbic reward circuit.